Anticoagulants on yield of bone marrow-derived mononuclear cells harvested from dogs - Harald Fernando Vicente de Brito; Tobias Fernandes-Filho; Fernanda de Lima Brandão; Patrícia Yukiko Montaño; Luciane Maria Laskoski; Rosangela Locatelli-Dittrich (Ciência Rural, 2015)
Cell therapy with bone marrow-derived mononuclear cells is an alternative to therapy with mesenchymal stem cell cultures. The aim of the present research was the comparison of the yield of bone marrow-derived mononuclear cells harvested from dogs with two different anticoagulants. Bone marrow was harvested from the iliac crest of five healthy dogs aged between 15 and 30 months, and the effect of two anticoagulant solutions, CPDA-1 (citrate phosphate dextrose adenine-1) and heparin, on the isolation of mononuclear cells was compared. Mononuclear cells were isolated in a density gradient and stained for CD9 and CD44 for characterization by flow cytometry. Means were compared using Student's paired t-test. Samples harvested with CPDA-1 yielded an average of 5.16x106 (±1.76x106) to 20.20x106 (±1.55x106) mononuclear cells/mL, whereas the yield of samples harvested with heparin varied between 4.56x106 (±0.69x106) and 24.30x106 (±2.12x106) mononuclear cells mL-1. By flow cytometry, mean percentage of double-stained cells varied from 1.96% (±0.64%) to 5.01% (±0.73%) for CPDA-1 and from 2.23% (±0.70%) to 7.27% (±0.97%) for heparin. No significant statistical differences were observed on yield or CD9 and CD44 expression. Further studies are recommended to assess efficacy of CPDA on mononuclear cell isolation.